Comparison of Q Angle and Tibial Torsion Among Premier League Futsal Players With and Without Hamstring Tightness - Hooman Minoonejad; Ehsan Tasoujian; Hossein Amiri; Reza Manteghi (Physical Treatments, 2016)
Purpose: Hamstring muscle is a two-jointed muscle, which is attached to the pelvis at one end and to tibia at the other. Contractures of the hamstring muscles affect the position of proximal and distal joints. The present study aims to compare the value of quadriceps angle (‘Q angle’) and tibial torsion among Premier League Futsal players with and without hamstring tightness. Methods: In this expost facto study, 30 male players, aged 18 to 25 years old, were non-randomly and purposefully selected as subjects. They were assigned to two 15-member groups, one containing players with hamstring tightness and the other without hamstring tightness. The goniometer was used to check the hamstring muscle tightness and measure the Q angle and tibial torsion. Independent t-test was used to analyze the data at a significance level of 0.05. SPSS version 21.0 was used for statistical analysis. Results: According to the findings of the present study, there was a significant difference in the value of Q angle and tibial torsion between the healthy athletes and group with hamstring tightness (P≤0.05). Conclusion: To prevent injuries in Futsal players with hamstring muscles tightness, special attention should be paid to the Q angle and tibial torsion.